Desenvolvimento de vacinas inativadas contra a Língua Azul e a Doença Epizoótica Hemorrágica para cervídeos: ensaios pré-clínicos. - Marco Tulio Gomes Campos (2020)
Bluetongue and epizootic hemorrhagic are viruses’ diseases characterized by the occurrence of hemorrhagic disorders in deer and are responsible for negative impacts on these species’ conservation. These diseases have BTV and EHDV viruses, respectively, as their etiologic agents. Vaccination is the most effective method of controlling and preventing these viruses. However, in Brazil, vaccines against BTV and EHDV are not licensed by regulatory organizations and there are no vaccines available for deer in national or foreign markets. In view of the above, the main objective of this research was the development of vaccines and the performance of pre-clinical trials with vaccine formulations containing samples of BTV-3, BTV-14, BTV-18, BTV-19, BTV- 22, BTV -24, EHDV-1 and EHDV-2 isolated in the biological reserve of Itaipu Binacional. The viral suspensions obtained in the laboratory were inactivated by beta-propiolactone, adjuvanted with 10% aluminum hydroxide and 40% saponin and distributed in two different vaccines: vaccine 1 (serotypes BTV-3, BTV-14, BTV-18 and BTV -19) and vaccine 2 (serotypes BTV-22, BTV-24, EHDV-1 and EHDV-2). Then, viral inactivation, sterility, inoculation, and potency tests were performed. The viral inactivation test confirmed complete virus inactivation, while the sterility test demonstrated the absence of bacterial growth. The inoculation test, carried out on four rabbits, did not show any adverse effects to vaccination. To perform the potency test, 15 rabbits were equally distributed in three experimental groups. The animals were vaccinated separately (G1 - Vaccine 1; G2 - Vaccine 2) and in combination (G3 - Vaccines 1 + 2) with three doses, administered at 0, 21 and 51 days of experimentation. The measurements of total antibodies and neutralizing antibodies of the potency test were carried out, respectively, by means of agar gel immunodiffusion (AGID), using the samples collected after 81 days of experimentation, and soroneutralization in microplate, using the samples collected at 0, 21, 51 and 81 days of experimentation. The results of the AGID indicated the presence of total antibodies in 100% of the animals tested for BTV, demonstrating that the antigens were able to induce humoral immune response. No AGID tests were performed for EHDV. In the soroneutralization test, the medians obtained indicated the absence of neutralizing antibodies for EHDV and the presence of neutralizing antibodies for BTV-18 virus (in the isolated vaccination), and BTV-18, BTV-19 and BTV-24 viruses (in the associated vaccination) in samples collected on the 81st day of experimentation. It was possible to observe that the formulations developed were not able to induce neutralizing antibody response for all serotypes and that the associated vaccination promoted a better humoral immune response. Our results will allow the development of new research for the formulation of vaccines for Brazilian deer.